Reflected Light Microscopy, Scanning Electron Microscopy, and Electron Microprobe Analysis of Submerged Bath Smelter Co-Ni Mattes - Christopher B. Vierrether (The Minerals, Metals and Materials Society, 1988)
Reflected light microscopy, scanning electron microscopy, and electron microprobe analysis have been used to determine the mineralogy, phase percentages, grain sizes, textures, and partitioning of cobalt and nickel in two cobalt-nickel rich mattes. These mattes were prepared by submerged bath smelting from a flotation cobalt-nickel concentrate containing 4.8% cobalt and 5.1% nickel. The concentrate was derived from lead-zinc-copper ores of the Viburnum Trend, southeast Missouri. Eleven discrete phases have been distinguished in the matte samples, three of which contain significant cobalt and nickel. The phases are cobaltpentlandite ((Co,Ni,Fe)9S8), cobalt-bearing marmatite ((Co,Fe,Zn)S), shandite (Ni3Pb2S2), bornite (Cu5FeS4), galena (PbS), magnetite (Fe3O4), pyrrhotite ((Co,Ni,Cu,Fe)1_xS), chalcocite (Cu2S), CuPbS phase, metallic copper, and metallic silver. Cobaltpentlandite and cobalt-bearing marmatite- occur in coarse grains (50 µm) that would separate readily during grinding, but shandite contains small (5 - 10um), abundant inclusions of pyrrhotite and bornite.. Some mineralogical variations between the two matte samples were due to differing degrees of oxidation during smelting,